Multidisciplinary therapies in the treatment of children with an autism spectrum disorder: a case report - Ramos, Laiene Barbosa; Silva, Luana Thaysa da; Godoy, Karolline Santos; Souza, Rosanea Meneses de; Franco, Carla Adriana Souza Oliveira (ARCHIVES OF HEALTH INVESTIGATION, 2021)
Purpose: To describe multidisciplinary interventions aimed at treating a child diagnosed with an autism spectrum disorder. Case description: The mother sought medical help for her son who exhibited language delays. He was agitated, did not respond to calls, and exhibited a delay in speech development. For psychopharmacological treatment, risperidone 1 mg/mL associated with vitamin D, was prescribed. Multidisciplinary therapies were proposed and applied according to the patient’s needs. In sessions with a speech therapist, he responded to all stimuli, demonstrating good interest in the proposed activities and maintained good eye contact. He performed several circuits to improve posture, image, laterality, and body scheme. After participating in hippotherapy supervised by several professionals, the child exhibited an improvement in social interaction, motor performance, especially in posture practice, and in communication. After interposing equine-assisted therapy with intellectual clinic sessions, he started activities at an inclusive school. Discussion: Multidisciplinary interventions demonstrated effectiveness and continuous and positive evolution in the patient. Studies reporting multidisciplinary therapies are relevant for demonstrating the importance of this method and the adaptation to the reality of each autistic patient.